Level of Patient Satisfaction in Dental Hospital of Universitas Jember in December 2019 - February 2020 - Dwi Prijatmoko; Elyda AA. Misrohmasari; Windy N. Eriyati (DiscoverSys Inc., 2021)
Objective: This study aims to determine the level of patient satisfaction at Universitas Jember Dental Hospital in December2019 – February 2020 based on patient status (clinic dental students’ patients and dentists’ patients). Dental Hospital Universitas Jember is one service provider that focuses on dental and oral health. Patients satisfaction is a result of comparing the services obtained with the patient’s expectations. The level of patient satisfaction is important for Dental Hospital Universitas Jember to improve service performance.Material and Methods: The study is a descriptive observational with cross sectional approach. Patients satisfaction was measured by Community Satisfaction Index (CSI) that consists of 14 indices.Results: Patient satisfaction score was 73.424 for clinic dental studentsâ€™Â patients and 76.917 for dentistsâ€™ patients. Both scores were categorized as a good level of satisfaction.Conclusion: Clinic dental studentsâ€™Â patients and dentistsâ€™Â patients were satisfied with the service at Universitas Jember Dental Hospital.